Process simulation of co-gasification system using adaro coal & Empty Fruit Bunches (EFB) in aspen hysys - Lee, Zhan Sheng (2016)
In recent years, alternatives to fossil fuels have been thoroughly discussed and researched. One of the great interests would be co-gasification, which is the process of converting multiple components of carbon-containing feedstock, specifically comprising both biomass and coal in this project, under high temperature with limited air supply in gasifier to produce synthetic gas (syngas). The biggest motivation here is co-gasification is able to utilise coal cleanly while employing biomass as the renewable energy source. Malaysia is one of the biggest producers and exporters of palm oil today, and having Empty Fruit Bunches (EFB) as the palm oil waste. Currently, there is no comprehensive simulation work on co-gasification of using EFB as the main feedstock yet. This has strongly driven the initiation in researching this co-gasification process. ASPEN HYSYS simulator is employed to perform the simulation. Steady state, isothermal model was built in ASPEN HYSYS with the assumptions of all chemical reactions take place at equilibrium state with neglected pressure drop in gasifier. A total of four parameters to be investigated in this simulation consist of temperature, equivalence ratio (ER), feedstock’s ratio of biomass to coal (B/C) and ratio of steam to biomass (S/B). A set of total twelve reactor models simulates various reaction zones of the entrained flow gasifier, comprising of pyrolysis of feedstock, combustion and char gasification. The results of simulation are compared with literature work to determine the error. Syngas composition decreases with the increase of ER. The increase of gasification temperature will increase CO and H2 in the syngas composition, so to increase the heating value of syngas. Increasing S/B will increase the production of CH4 and H2 at the expense of CO. For B/C ratio parameter study, the result shows that plain biomass gasification is not efficient as compared to hybrid feedstock – biomass and coal.